CO2-free hydrogen production via microwave-driven methane pyrolysis. (5th May 2023) - Dadsetan, Mehran; Khan, Mohammad Fawaz; Salakhi, Mehdi; Bobicki, Erin R.; Thomson, Murray J.
Abstract: Hydrogen will play an integral role in achieving net-zero emissions by 2050. Many studies have been focusing on green hydrogen, but this method is highly electricity intensive. Alternatively, methane pyrolysis can produce hydrogen without direct CO2 emissions and with modest electricity inputs, serving as a bridge from fossil fuels to renewable energies. Microwaves are an efficient method of adding the required energy for this endothermic reaction. This study introduces a new method of CO2 -free hydrogen production via non-plasma methane pyrolysis using microwaves and carbon products of this process. Carbon particles in the fluidized bed absorb microwave energy and create a hot medium (>1200 °C) in contact with flowing methane. As a result, methane decomposes into hydrogen and solid carbon achieving over 90% hydrogen selectivity with ∼500 cumulative hours of experiments This modular pyrolysis system can be built anywhere with access to natural gas and electricity, enabling distributed hydrogen production. Graphical abstract: Image 1 Highlights: CH4 pyrolysis via microwave heating of fluidized carbon pellets to produce CO2 -free H2 . Utilized the carbon product of the pyrolysis process as the microwave receptor. Steady methane conversion was achieved for 500 cumulative hours of the experiment. More than 90% hydrogen selectivity obtained at temperatures over 1000 °C